Motivation in learning mathematics among high school students in Ningbo, China - Mengyao, He; Ismail, Zaleha; Ismail, Norulhuda; Xueting, He (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Motivation plays a crucial role in enhancing students' achievement in mathematics, as motivated students are more likely to engage actively with the subject. However, in China, there is a concerning trend of declining motivation among students toward mathematics, with many exhibiting avoidance behaviors. Despite Ningbo's significance as a major city in China, there is a lack of studies and surveys addressing students' motivation in mathematics learning. This study addresses this gap by employing a questionnaire based on Keller’s ARCS (Attention, Relevance, Confidence, Satisfaction) model, which has been proven effective in measuring students’ motivation. The survey, conducted among 384 high school students in Ningbo, China, aimed to assess their motivation levels in mathematics learning. Descriptive statistical analysis was performed using SPSS Statistics 29 to calculate the mean and percentage for each item. The results revealed that the motivation level among high school students in Ningbo is notably low. Two significant factors contributing to this low motivation were identified: students’ lack of confidence due to the perceived difficulty of mathematics and the belief that mathematics is not closely related to real life.